Artificial intelligence and image processing applications for high-throughput phenotyping - Margapuri, Venkata Siva Kumar (Kansas State University, 2022)
The areas of Computer Vision and Scientific Computing have witnessed rapid growth in the last decade with the fields of industrial robotics, automotive and healthcare acting as the primary vehicles for research and advancement. However, related research in other fields, such as agriculture, remains an understudied problem. This dissertation explores the application of Computer Vision and Scientific Computing in an agricultural domain known as High-throughput Phenotyping (HTP). HTP is the assessment of complex seed traits such as growth, development, tolerance, resistance, ecology, yield, and the measurement of parameters that form more complex traits. The dissertation makes the following contributions: The first contribution is the development of algorithms to estimate morphometric traits such as length, width, area, and seed kernel count using 3-D graphics and static image processing, and the extension of existing algorithms for the same. The second contribution is the development of lightweight frameworks to aid in synthetic image dataset creation and image cropping for deep neural networks in HTP. Deep neural networks require a plethora of training data to yield results of the highest quality. However, no such training datasets are readily available for HTP research, especially on seed kernels. The proposed synthetic image generation framework helps generate a profusion of training data at will to train neural networks from a meager samples of seed kernels. Besides requiring large quantities of data, deep neural networks require the input to be a certain size. However, not all available data are in the size required by the deep neural networks. The proposed image cropper helps to resize images without resulting in any distortion, thereby, making image data fit for consumption. The third contribution is the design and analysis of supervised and self-supervised neural network architectures trained on synthetic images to perform the tasks of seed kernel classification, counting and morphometry. In the area of supervised image classification, state-of-the-art neural network models of VGG-16, VGG-19 and ResNet-101 are investigated. A Simple framework for Contrastive Learning of visual Representations (SimCLR) [137], Momentum Contrast (MoCo) [55] and Bootstrap Your Own Latent (BYOL) [123] are leveraged for self-supervised image classification. The instance-based segmentation deep neural network models of Mask R-CNN and YOLO are utilized to perform the tasks of seed kernel classification, segmentation and counting. The results demonstrate the feasibility of deep neural networks for their respective tasks of classification and instance segmentation. In addition to estimating seed kernel count from static images, algorithms that aid in seed kernel counting from videos are proposed and analyzed. Proposed is an algorithm that creates a slit image which can be analyzed to estimate seed count. Upon the creation of the slit image, the video is no longer required to estimate seed count, thereby, significantly lowering the computational resources required for the estimation. The fourth contribution is the development of an end-to-end, automated image capture system for single seed kernel analysis. In addition to estimating length and width from 2-D images, the proposed system estimates the volume of a seed kernel from 2-D images using the technique of volume sculpting. The relative standard deviation of the results produced by the proposed technique is lower (better) than the relative standard deviation of the results produced by volumetric estimation using the ellipsoid slicing technique. The fifth contribution is the development of image processing algorithms to provide feature enhancements to mobile applications to improve upon on-site phenotyping capabilities. Algorithms for two features of high value namely, leaf angle estimation and fractional plant cover estimation are developed. The leaf angle estimation feature estimates the angle between stem and leaf for images captured using mobile phone cameras whereas fractional plant cover is to determine companion plants i.e., plants that are able to co-exist and mutually benefit. The proposed techniques, frameworks and findings lay a solid foundation for future Computer Vision and Scientific Computing research in the domain of agriculture. The contributions are significant since the dissertation not only proposes techniques, but also develops low-cost end-to-end frameworks to leverage the proposed techniques in a scalable fashion.
Keywords: High-throughput phenotyping; Computer vision; Image processing; Artificial intelligence